Europe in the Neolithic the creation of new worlds - Whittle, A. W. R. 1949- (Univ. Pr., 1996)
Unique in its broad and up-to-date coverage of long-term processes of change on a continental scale, this completely rewritten and revised version of Whittle's Neolithic Europe: a survey reflects radical changes in the evidence and in interpretative approaches over the past decade
Keywords: Neolithicum; Funde; Neolithic period -- Europe; Neolithikum; Europa; Europe -- Antiquities